Universities preparedness to implement the federal state: educational standards: organizational aspect - V. . Zyryanov; I. . Kotlobovsky; A. . Sinyakov (Высшее образование в России)
The article continues to present the results of monitoring the implementing effectiveness of the federal state educational standards (FSES) of higher education institutions conducted by the Association of Classical Universities of Russia, the Association of Technical Universities and the Comprehensive Research Institute of Education MSU at the turn of 2011 – the beginning of 2012. The article presents data on the universities organizational readiness to implement the FGOS, gives an assessment of the readiness state, identifies «hot spots», which create problems in this way. Also the article draws conclusions aimed at helping universities in setting benchmarks and parameters entering the tempo and rhythm of the educational activity, regulated by FSES.